2017
DOI: 10.1007/s11906-017-0731-4
|View full text |Cite
|
Sign up to set email alerts
|

DOCA-Salt Hypertension: an Update

Abstract: Hypertension is a multifaceted disease that is involved in ∼40% of cardiovascular mortalities and is the result of both genetic and environmental factors. Because of its complexity, hypertension has been studied by using various models and approaches, each of which tends to focus on individual organs or tissues to isolate the most critical and treatable causes of hypertension and the related damage to end-organs. Animal models of hypertension have ranged from Goldblatt's kidney clip models in which the origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 77 publications
6
118
1
5
Order By: Relevance
“…These connections contribute to the pronounced increase of sympathetic nerve activity in hypertension (Guyenet, ; Ye et al . ; Basting & Lazartigues, ).…”
Section: Discussionmentioning
confidence: 99%
“…These connections contribute to the pronounced increase of sympathetic nerve activity in hypertension (Guyenet, ; Ye et al . ; Basting & Lazartigues, ).…”
Section: Discussionmentioning
confidence: 99%
“…Deoxycorticosterone acetate‐salt rats show hypertension resulting from hypervolaemia induced by hyperaldosteronism and high salt intake followed by increasing renal reabsorption of water and sodium . In this study, the pressor responses to PNS in the isolated mesenteric vascular bed with the intestinal tract in DOCA‐salt rats were significantly lower than those in sham rats.…”
Section: Discussionmentioning
confidence: 51%
“…When DOCA‐treated rats are given NaCl‐containing water, they display volume‐dependent hypertension (DOCA‐salt rat) . The DOCA‐salt rat has been used as a model of hypertension since the 1970s . The Dahl S rat, a genetic model of hypertension, is well known for its rapid elevation in blood pressure when placed on a high‐sodium diet (4%–8% NaCl) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our lab and others showed that DOCA-salt hypertension, a model of neurogenic hypertension, is associated with autonomic dysfunction and elevated sympathetic activation. 4, 21 Autonomic function was identical at baseline between sham-treated WT and B1RKO mice (Figure 2C–E). DOCA-salt administration resulted in significant increases in both cardiac (increased bradycardia to propranolol, −145 ±21 beats/minutes, P<0.01 vs. sham) and vascular (decreased MAP to chlorisondamine, −88 ±7 mmHg, P<0.01 vs. sham) sympathetic drive, as well as reduction of vagal tone (reduced tachycardia to atropine, +111 ±8 beats/minute, P<0.01 vs. sham) in WT mice, which were normalized in B1RKO mice (−72 ±13 beats/minutes, −59 ±3 mmHg, and +165 ±6 beats/minute, respectively, P<0.01 vs. WT+DOCA).…”
Section: Resultsmentioning
confidence: 86%
“…Since DOCA-salt hypertension is mainly driven by an alteration in central mechanisms regulating BP, 21 we further investigated the importance of kinin B1R in BP control, using a brain targeted pharmacological approach. Chronic icv infusion of R715, a B1R specific antagonist, attenuated the development of DOCA-salt hypertension.…”
Section: Discussionmentioning
confidence: 99%